2014
DOI: 10.1155/2014/919323
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Survival in Patients Treated Surgically for Recurrent Metastatic Uterine Leiomyosarcoma

Abstract: Background. Uterine leiomyosarcoma (LMS) is a rare diagnosis, which is seldom cured when it recurs with metastatic disease. We evaluated patients who present with first time recurrence treated surgically to determine prognostic factors associated with long-term survival. Methods. Over a 16-year period, 41 patients were operated on for recurrent uterine sarcoma. Data examined included patient age, date of initial diagnosis, tumor histology, grade at the initial diagnosis, cytopathology changes in tumor activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
0
13
0
3
Order By: Relevance
“…Zivanovic et al . showed that FIGO stage does not perform well in terms of predicting overall survival (OS) in patients with ULMS [ 4 6 ]. C-reactive protein (CRP) is a readily available and cheap laboratory parameter, that is widely used in clinical routine as the most important acute phase serum protein to monitor infection.…”
Section: Introductionmentioning
confidence: 99%
“…Zivanovic et al . showed that FIGO stage does not perform well in terms of predicting overall survival (OS) in patients with ULMS [ 4 6 ]. C-reactive protein (CRP) is a readily available and cheap laboratory parameter, that is widely used in clinical routine as the most important acute phase serum protein to monitor infection.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal treatment for recurrent uterine sarcomas remains unclear. These tumors are relatively chemoand/or radio-resistant, and certain studies have previously evaluated the effectiveness of SCS in patients with recurrent uterine sarcomas (11,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…SCS for patients who have pulmonary recurrent disease has been reported to lead to improved survival, particularly in those with unilateral disease, a smaller number of resected metastases (<3), a smaller tumor (<3 cm) and a longer DFI (<6, or 12 months) (8)(9)(10). However, studies on SCS for extra-pulmonary recurrences of uterine sarcomas are limited, and have only small sample sizes (4,11,(14)(15)(16)(17). Leitao et al (14) reported that optimal surgical resection may improve the survival of patients with either pulmonary or extra-pulmonary metastases, after retrospectively surveying 41 patients with recurrent LMS (including 28 patients who had non-thoracic recurrences).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations